REKONSTRUKSI PEMAHAMAN HADIS GENDER FATIMA MERNISI - Fatimah Fatmawati (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2019)
This paper discusses Fatima Mernisi’s hermeneutics in understanding misogynic traditions. The meaning of misogynic traditions is a hadith that has a bater of women. The methodology used by the Mernisi is called double investigation, which is an investigation of historical and methodological aspects. The First step is finding the historical context of hadith. At this step, Mernisi analyzes the socio-historical situation when the text is spoken / practiced by the Prophet. Second, methodological step, which is to criticize sanad and situations when the hadith is narrated again. When, why, whom, and how the text was narrated again by the first transmitter. In analyzing hadith, Mernisi uses the methodology which has been pioneered by classical scholars, criticism of sanad. A significant difference is that criticism of Sanad is used as a knife of analysis in verifying the credibility of shahabah as the first transmitter. That is, in the realm of the scientific study of hadith, shahabah are not immune to criticism. As a result, Mernisi found that several hadiths with nuanced misogyny had to be rejected because the first transmitter did not fulfill the criteria adalah. Unfortunately, Mernisi only emphasized the authenticity aspect of the hadith, not the contextual aspects. This methodology seems to be suitable only for certain traditions which are problematic, but cannot be universally applied to all misogynyc traditions..